An overview of plant microbial fuel cells (PMFCs): Configurations and applications. (August 2019) - Kabutey, Felix Tetteh; Zhao, Qingliang; Wei, Liangliang; Ding, Jing; Antwi, Philip; Quashie, Frank Koblah; Wang, Weiye
Abstract: The depletion of non-renewable energy resources has led to the exploitation of alternative renewable sources such as solar energy, which is mainly employed to generate electricity using conventional photovoltaic cells. In recent years, other alternative bioelectrochemical systems such as plant microbial fuel cells (PMFCs) has been developed to generate electricity via biological interactions of plants and microbes in the presence of sunlight. Compared to the photovoltaic cells, PMFCs can also generate power continuously, being implemented on agricultural lands without any obstruction to food cultivation/production processes or even in the fields unsuitable for food production. To explore and optimize the use of living plants for sustainable power generation in PMFCs, the key fundamental aspects peculiar to PMFCs were comprehensively reviewed. Subsequently, various reported configurations of PMFCs embedded with vascular plants, macrophytes and bryophytes as well as their combination with constructed wetlands were evaluated and discussed. So far, PMFCs could be applied in the fields of wastewater treatment, polluted sediment and surface water remediation, greenhouse gas mitigation and biosensing. Finally, the prospects and challenges of PMFCs for full-scale applications were also presented. Overall, PMFCs will become alternative renewable energy sources to reduce energy scarcity and related environmental issues when they are scaled up and applied in-situ . Highlights: PMFC is a novel system to generate bioelectricity using living plants and bacteria. Supporting matrix, plants and microorganisms are key components of PMFCs. PMFC operation relies on plant rhizodeposition for bioelectricity generation. PMFCs with vascular plants, macrophytes, bryophytes and CWs are four configurations. PMFCs find their wide applications in removing various pollutants and biosensing.